2021
DOI: 10.3126/njh.v18i2.40401
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Induced Nephropathy and its predictors after Primary Percutaneous Intervention

Abstract: Background and Aims: Worldwide many patients are receiving intravascular contrast media (CM) during interventional procedures. Contrast media are used to enhance visualization and guide percutaneous coronary interventions (PCI).1 However, the use of CM also carries the risk of complications and it is important to be aware of these complications. Complications with CM range from mild symptoms to life-threatening conditions like anaphylaxis, hypotension and renal dysfunction and contrast-induced nephropathy (CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…In general, observably less amount of contrast is used in our study compared to other studies. 18,27 However, we still observed contrast volume ≤ 100 ml as an independent predictor of CIN which is consistent with the findings of Adhikari et al 23…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, observably less amount of contrast is used in our study compared to other studies. 18,27 However, we still observed contrast volume ≤ 100 ml as an independent predictor of CIN which is consistent with the findings of Adhikari et al 23…”
Section: Discussionsupporting
confidence: 92%
“…22 The predictor assessment of the present study revealed that The older patients had a higher risk, as expected, and our study found comparable results to those where the mean age for CIN occurrence was higher. 23 In our study, we discovered that patients developing CIN had a greater age 65.9 ± 9.7 versus 57.8 ± 11.8 in patients who did not develop CIN and it was also observed to be the independent predictor in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 53%